Pembinaan oleh PHDI Melalui Metode Dharma Tula dalam Meningkatkan Sradha Bhakti Umat Hindu di Desa Sukorejo Kecamatan Bangorejo Kabupaten Banyuwangi - Eko Prastyo; Relin D. E.; I Made Redana (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
The development of the Hindu community in Sukorejo Village, Bangorejo District, Bnayuwangi Regency is one of the most important aspects in building a religious society. Proselytization, the decline in the quantity and quality of Hindus, as well as the in creasing spread of intolerant behavior, have created growing concerns. Therefore, guidance in the form of dharma tula emerges as a refreshing response to the increasingli significant changes. This study is a descriptive qualitative research based on data collection methods such as observation, interviews, literature studies, and document studies. The collected data were and then continued to the data analysis stage. This research employs three main theories to analyze the phenomenom, namely deconstruction theory, role theory, and behaviorstic theory. Based  on the results of the data analysis and discussion, the researsher found several findings summarized as follows: 1) the form of Hindu community development using the dharma tula method is conducted trhough discussion activities between Hindus and the speakers of dharma tula. 2) the functions of Hindu community development through the dharma tula method consist of three aspects, namely guidance as a form education, strengthening Hindu religious teachings, and reinforcing the sradha bhakti of Hindus in Sukorejo Village. 3) The implication of Hindu community development through the dharma tula method is the strengthening of the sradha bhakti of Hindus in Sukorejo Village in cognitive, affective, and practical aspects.